Patent, Technology, and The Role of University - Sardjono, Agus (Indonesia Law Review, 2011)
University has significant contribution to the development of nanotechnology. The role of university can be implemented through the TTLO, particularly in an effort to build a bridge for bottom-up nanotechnology for commercial purposes. There will be an increasingly significant link between the patent system and the university role in the development of nanotechnology.